Pengaruh Model Pergerakan Node terhadap Konsumsi Energi Protokol Routing Location Aided Routing (LAR) pada Mobile Ad Hoc Network (MANET) - Tommy Bona Hamonangan Sitorus; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Nodes that have mobile properties form a network called MANET. This study uses protocol routing that is reactive, namely Location Aided Routing (LAR) where the protocol routing uses the position information of each node that comes from the Global Positioning System (GPS). From the use of these techniques and position information, the area to search for routes is reduced and restricted. Along with this, the energy consumed by each node needs to be reviewed. The performance of the Location Aided Routing (LAR) routing protocol can be affected by node movement. This movement node can pose a risk of disconnection between nodes and routing unsuccessful. The performance of the protocol is routing directly proportional to energy consumption. This study uses the number of different nodes and node movements to conduct test scenarios. In the 30 node scenario, the largest total energy consumption occurs in the movement model the Random Waypoint node and has a difference with the total energy consumption of the Random Direction node movement model of 351.491386 Joules. Conversely, in the scenario 45 and 60 nodes the largest total dominant energy consumption is when employing the Random Direction node movement model. In the Random Waypoint node movement model, the average energy consumption scenario decreases and increases regarding node addition. Whereas in Random Direction, the average energy consumption continues to increase. The amount of energy consumption is affected by the number of nodes and the different node movement models.